What are Future Curing Lights Technology Trends? - P. Bradna; L. Comba; J. Froněk; D. Houšová (Czech Dental Chamber, 2010)
Over the recent years, dental curing lights as well as light-cured materials have been undergoing rapid development, which makes choosing a curing light guaranteeing the optimal polymerization degree difficult. The paper summarizes critical characteristics of curing lights necessary for reliable polymerization of light-cured composite materials, glass-ionomer cements and adhesive systems with different types of photoinitiators. The effect of emission-spectrum width on the polymerization degree of composite material is documented with polymerization of two typical composite materials with different photoinitiators and light-cured using quartz-tungsten-halogen lamp and LED lights with narrow and wide emission band. Values of surface Knoop hardness numbers revealed that among currently available curing lights, in particular LED with two or more types of diodes emitting broad-range blue light achieve the versatility and efficiency of halogen lights, currently the gold standard in light curing.